Online task scheduler in 3D-MCPs with TADVA - Liao, Chien-Hui; Wen, Charles Hung-Pin (Chronic diseases and translational medicine, 2018)
Hotspots occur frequently in three-dimensional (3D) multi-core processors (3D-MCPs), and they may adversely impact both the reliability and lifetime of a system. The authors present dynamic-voltage-assignment (DVA) strategies that reduce hotspots in and optimise the performance of 3D-MCPs by pre-emptively selecting voltages among low-power and high-performance operating modes. The proposed DVA strategies can be employed in online, thermally constrained task schedulers. Three DVA strategies, random DVA, thermal-aware DVA (TADVA) and TADVA2.0, are proposed to reduce the temperature increase in 3D-MCPs by pre-emptively and dynamically estimating the optimum VAs for all cores in the processor during runtime once the chip begins operating. In particular, TADVA2.0 uses the temperature-variation rates of the cores and takes into account two important thermal behaviours of 3D-MCPs that can effectively limit the temperature increase in 3D-MCPs. Experimental results indicate that, when compared with two previous online thermally constrained task schedulers, the proposed task scheduler with their novel DVA strategy can reduce hotspot occurrences by ∼60% and improve throughput by ∼8%. These results indicate that the proposed TADVA2.0 strategy is an effective technique for suppressing hotspot occurrences and optimising throughput for 3D-MCPs subject to thermal constraints.